1995
DOI: 10.1021/bi00007a028
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Contributes to the Rapid Inactivation of Specific Secondary Donors of the Photosystem II Reaction Center during Photodamage of Manganese-Depleted Photosystem II Membranes

Abstract: The role of superoxide in the mechanism of photoinactivation of the secondary donors of the reaction center of photosystem II membranes depleted of Mn by extraction with NH2OH plus EDTA (NH2OH/EDTA-PSII) was assessed. EPR analyses (g = 2 region) in continuous light, optical kinetic spectrophotometric analyses of P680+ and Car+, and AT-band emission measurements were made after various durations of weak and strong light treatment of NH2OH/EDTA-PSII in the presence and absence of superoxide dismutase, or of PSII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 47 publications
3
28
1
1
Order By: Relevance
“…Asc is not only an alternative electron donor to PSII but also a direct scavenger of reactive oxygen species (ROS) produced during donor-sideinduced photoinhibition (e.g. Chen et al, 1995;Spetea et al, 1997). To ascertain that the Asc dependence correlates with the ability of Asc to act as a PSII electron donor, we incubated intact vtc2-3 leaves in DPC solution (1 mM DPC, an artificial electron donor of PSII, with no ROS-scavenging properties) before the heat treatment.…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Asc is not only an alternative electron donor to PSII but also a direct scavenger of reactive oxygen species (ROS) produced during donor-sideinduced photoinhibition (e.g. Chen et al, 1995;Spetea et al, 1997). To ascertain that the Asc dependence correlates with the ability of Asc to act as a PSII electron donor, we incubated intact vtc2-3 leaves in DPC solution (1 mM DPC, an artificial electron donor of PSII, with no ROS-scavenging properties) before the heat treatment.…”
Section: Parametersmentioning
confidence: 99%
“…Experiments on PSII preparations and on leaves with chemically inactivated OECs indicate that the very high sensitivity of PSII to light appears to be caused by the impaired electron donation from the OEC. This, in turn, results in strong accumulation of highly oxidizing radicals, P680 + , Tyr Z + , and superoxide (Chen et al, 1995) or hydroxyl radicals (Spetea et al, 1997), and leads to a rapid inactivation and degradation of PSII reaction centers (Callahan et al, 1986;Blubaugh and Cheniae, 1990;Jegerschöld and Styring, 1996). This type of photodamage is called weak light or donor-side-induced photoinhibition.…”
mentioning
confidence: 99%
“…2+ is an essential ion in the photoassembly reaction in all native PSIIWOCs examined to date. If Ca 2+ is left out of the solution, binding and photooxidation of many more Mn 2+ occurs (up to 20) to the apo-WOC-PSII protein and no O 2 evolution activity is observable [45,58]. The relative binding affinities of various divalent metals (Mg 2+ , Ca 2+ , Mn 2+ , Sr 2+ ), and the oxo-cation UO 2 2+ have been characterized [11,59,60].…”
Section: 21mentioning
confidence: 99%
“…Previous studies suggested that H 2 O 2 is generated from the PSII acceptor side when the oxidation of Q A 2 is perturbed (Schrö der and Å kerlund, 1990), or from the PSII donor side when the function of the Mn cluster is impaired (Schrö der and Å kerlund, 1986;Fine and Frasch, 1992;Hillier and Wydrzynski, 1993;Klimov et al, 1993;Arató et al, 2004). PSII depleted of the Mn cluster has also been reported to generate O 2 2 efficiently (Chen et al, 1995). Since both the acceptor side and donor side reactions of PSII were impaired in DPsbP leaves, H 2 O 2 may present around PSII and attack the Mn cluster.…”
Section: Higher-plant Psbp Is Required To Maintain the Active Mn-ca-cmentioning
confidence: 99%